EMbedding and Backscattered Scanning Electron Microscopy: A Detailed Protocol for the Whole-Specimen, High-Resolution Analysis of Cardiovascular Tissues - Mukhamadiyarov, Rinat A.; Bogdanov, Leo A.; Glushkova, Tatiana V.; Shishkova, Daria K.; Kostyunin, Alexander E.; Koshelev, Vladislav A.; Shabaev, Amin R.; Frolov, Alexey V.; Stasev, Alexander N.; Lyapin, Anton A.; Kutikhin, Anton G. (Frontiers in Cardiovascular Medicine, 2021)
Currently, an ultrastructural analysis of cardiovascular tissues is significantly complicated. Routine histopathological examination and immunohistochemical staining suffer from a relatively low resolution of light microscopy, whereas a fluorescence imaging of plaques and bioprosthetic heart valves yields a considerable background noise from the convoluted extracellular matrix that often results in a low signal-to-noise ratio. Besides, sectioning of calcified or stent-expanded blood vessels or mineralised heart valves leads to a critical loss of their integrity, demanding other methods to be developed. Here we designed a conceptually novel approach which combines conventional formalin fixation, sequential incubation in heavy metal solutions (osmium tetroxide, uranyl acetate or lanthanides, and lead citrate), and embedding of the whole specimen into epoxy resin to retain its integrity while accessing the region of interest by grinding and polishing. Upon the carbon sputtering, the sample is visualised by means of backscattered scanning electron microscopy. The technique fully preserves calcified and stent-expanded tissues, permits a detailed analysis of vascular and valvular composition and architecture, enables discrimination between multiple cell types (including endothelial cells, vascular smooth muscle cells, fibroblasts, adipocytes, mast cells, foam cells, foreign-body giant cells, canonical macrophages, neutrophils, and lymphocytes) and microvascular identities (arterioles, venules and capillaries), and gives a technical possibility for quantitating number, area and density of the blood vessels. Hence, we suggest that our approach is capable of providing a pathophysiological insight into cardiovascular disease development. The protocol does not require a specific expertise and can be employed in virtually any laboratory having a scanning electron microscope.